Pemberdayaan Perempuan Melalui Pelatihan Kerajinan Decoupage: Membangun Jiwa Wirausaha Kreatif Ibu-Ibu Dharma Wanita - Devi Permatasari; Naila Najihah; Sri Sulistyowati (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This community service program aims to develop the creative entrepreneurial competence of Dharma Wanita LLDIKTI Region 6 members through decoupage craft training encompassing three dimensions: (1) knowledge of creative business opportunities in the modern era, (2) technical skills in producing decoupage products on woven wallet media, and (3) basic understanding of product packaging and market value. Implementation followed three stages: preparation (partner coordination and module development), execution (socialization, demonstration, and hands-on practice), and evaluation (pre-test/post-test and skill observation). Twenty participants took part in the program. Results showed an improvement in creative entrepreneurship knowledge with an average gain score of 0.68, all participants (100%) successfully completed one decoupage product, 85% produced products of good aesthetic quality, and participants’ confidence to start a business increased from 35% to 90%. These findings indicate that product-based skill training is effective in building the creative entrepreneurship foundation of women and can serve as a sustainable empowerment model within Dharma Wanita organizations.